Detailed quantum mechanical, molecular docking, QSAR prediction, photovoltaic light harvesting efficiency analysis of benzil and its halogenated analogues. Issue 11 (November 2019) - Mary, Y. Shyma; Mary, Y. Sheena; Resmi, K.S.; Kumar, Veena S.; Thomas, Renjith; Sureshkumar, B.
Abstract: The structural, spectroscopic various physico-chemical and biological characteristics of the organic molecule benzil (BZL) and derivatives, 1, 2-bis(4-methylphneyl)-1, 2-ethanedione (DMB), 4, 4′-difluorobenzil (DFB), 4, 4′-dichlorobenzil (DCB) and 4, 4′-dibromobenzil (DBB) have been studied by various computational methods. The experimental and scaled simulated Raman and IR spectra were compared and found close agreement. Assignments of important peaks are also presented. Detailed information pertaining to the local and global reactivity and other properties like electrophilic and nucleophilic characteristics were analysed. The hyperactive pressure was measured in terms of polarizability and corresponding biological properties were validated to identity reactive sites. Prediction of Activity Spectral Studies (PASS) predicts the biological activity of the compounds and it is found that the candidate molecules can be used as feruloyl esterase inhibitor, bisphosphoglycerate phosphatase inhibitor and Prolylaminopeptidase inhibitor. The crystals structures of those receptors are taken from the protein data bank and docking studies indicates stable complex with the receptors and candidate molecules. Light harvesting efficiency, followed by photovoltaic modelling shows that DMB is the best compound to be used in the DSSC to get the best output. Abstract : Organic chemistry; Theoretical chemistry; Pharmaceutical chemistry; DFT; Docking; NLO; MEP; DSSC